A new 4H-SiC hydrogen sensor with oxide ramp termination. (February 2016) - Pascu, Razvan; Kusko, Mihaela; Craciunoiu, Florea; Pristavu, Gheorghe; Brezeanu, Gheorghe; Badila, Marian; Avramescu, Viorel
Abstract: A Pd/SiO2 /4H-SiC MOS capacitor with oxide ramp termination has been fabricated and its utilization for hydrogen (H2 ) sensing is reported. The grown oxide and oxide-semiconductor interface properties investigation by electrical measurements on test capacitors gave an electron tunneling barrier ( Φ b =2.62 eV) very close to the theoretical one ( Φ b =2.7 eV). This large electron tunneling barrier shows good oxide insulating properties. The density of interface states ( D it ) has a relatively low value for a 31 nm thick oxide, with no post-oxidation annealing. The gas sensing capabilities of the SiC-MOS capacitor were tested at elevated temperatures, for different H2 concentrations. The sensor response increased with temperature, the maximum sensitivity (80%) being reached at 450 K. The flat band voltage ( V FB ) is left shifted up to 1.51 V at 20 ppm H2 concentration, showing sensitivity at low gas concentrations. The response/recovery times of about 5 to 6 s, respectively, were measured at 10, 000 ppm hydrogen in nitrogen. These results recommend this capacitor structure for H2 detection.